Penyuluhan penanganan panen dan pasca panen padi gogo di Desa Pollewani, Kecamatan Tubbi Taramanu, Polewali Mandar - Syah, Ikrar Taruna; HM., Rahmaniah; Utami, Rahmawati Ning (Agriculture and Forestry Faculty, Universitas Sulawesi Barat, 2025)
Polewali Mandar Regency comprises 16 sub-districts, with the most significant administrative area being Tubbi Taramanu Sub-district, which is one reason this region remains less